2011
DOI: 10.4049/jimmunol.1004151
|View full text |Cite
|
Sign up to set email alerts
|

Memory CCR6+CD4+ T Cells Are Preferential Targets for Productive HIV Type 1 Infection Regardless of Their Expression of Integrin β7

Abstract: HIV type 1 infection is associated with a rapid depletion of Th17 cells from the GALT. The chemokine receptor CCR6 is a marker for Th17 lineage polarization and HIV permissiveness in memory CD4+ T cells. CCR6+ T cells have the potential to migrate into the GALT via the gut-homing integrin α4β7, a newly identified HIV-gp120 binding receptor. In this study, we investigated whether memory T cells coexpressing CCR6 and integrin β7 are selective HIV targets and whether retinoic acid (RA)-induced imprinting for gut-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
165
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 76 publications
(127 reference statements)
13
165
0
Order By: Relevance
“…CD4 + Th17 cells are among the earliest HIV/SIV preferential targets and play a crucial role in HIV pathogenesis. 86,[94][95][96][97] In contrast to the significant semen-induced increase in DCs and LCs in the female genital epithelium, no or modest increases in FRT CD4 + T cell density have been detected following semen exposure. 23,38 At the same time, due to CCL20, a small number of these highly susceptible to HIV-1 CD4 + Th 17 cells can infiltrate the mucosal epithelium or migrate to local lymph nodes.…”
Section: Seminal Plasma and Female Genital Tract Immune Responsementioning
confidence: 80%
See 1 more Smart Citation
“…CD4 + Th17 cells are among the earliest HIV/SIV preferential targets and play a crucial role in HIV pathogenesis. 86,[94][95][96][97] In contrast to the significant semen-induced increase in DCs and LCs in the female genital epithelium, no or modest increases in FRT CD4 + T cell density have been detected following semen exposure. 23,38 At the same time, due to CCL20, a small number of these highly susceptible to HIV-1 CD4 + Th 17 cells can infiltrate the mucosal epithelium or migrate to local lymph nodes.…”
Section: Seminal Plasma and Female Genital Tract Immune Responsementioning
confidence: 80%
“…CCL20 is the only chemokine ligand for the CCR6 receptor, expressed by subsets of DCs, particularly precursors of LCs, and memory T cells including CD4 + Th17 T cells. 74,86,87 LCs, present in cervicovaginal mucosa, are among the primary targets of HIV-1/SIV. 30,31,88,89 LCs are able to capture HIV-1 virions and transport them to the draining lymph nodes where the virions can be transmitted to T cells for productive infection, 27,[88][89][90] although there is some evidence to suggest viral particles captured by LCs are internalized and rendered incapable of infection.…”
Section: Seminal Plasma and Female Genital Tract Immune Responsementioning
confidence: 99%
“…Others have found that increased CCR5 surface expression could be correlated with the susceptibility of early differentiated IL-17 + CD4 T cells, leading the authors to postulate that this may be a possible mechanism for viral permissiveness [39]. One earlier study [40] used all-trans-retinoic acid (ATRA) (a compound that upregulates a4b7 integrin expression) to study the mechanisms of the preference of the R5-HIV strain to infect CCR6 + memory T cells over CCR6 À cells. Indeed, pseudotyped HIV that enter host cells independently of chemokine co-receptors showed a preference for infection of ATRA-treated CCR6 + cells (over untreated CCR6 + cells, and compared with treated and untreated CCR6 À/À cells), suggesting that the mechanism by which HIV is selective towards ATRA-treated CCR6 + cells is likely through post-entry mechanisms such as integration and transcription [40].…”
Section: Involvement Of Ccr6 In Cellular Hiv Pathogenesis T H 17 Cellsmentioning
confidence: 99%
“…One earlier study [40] used all-trans-retinoic acid (ATRA) (a compound that upregulates a4b7 integrin expression) to study the mechanisms of the preference of the R5-HIV strain to infect CCR6 + memory T cells over CCR6 À cells. Indeed, pseudotyped HIV that enter host cells independently of chemokine co-receptors showed a preference for infection of ATRA-treated CCR6 + cells (over untreated CCR6 + cells, and compared with treated and untreated CCR6 À/À cells), suggesting that the mechanism by which HIV is selective towards ATRA-treated CCR6 + cells is likely through post-entry mechanisms such as integration and transcription [40]. Subtle molecular differences in T H 17 cells may also be responsible for their increased permissiveness to HIV infection with genome-wide transcriptional profiles of T H 17 versus T H 1 cells (as 'controls') revealing an increased expression of molecules responsible for promoting TCR signalling that are essential for HIV transmission (e.g.…”
Section: Involvement Of Ccr6 In Cellular Hiv Pathogenesis T H 17 Cellsmentioning
confidence: 99%
“…To understand how natural hosts preserve Th17 cells and mucosal immunity might be central to the development of therapeutic interventions aimed at improving mucosal immunity in HIV-infected individuals. While the exact cause accounting for this phenotype is still unclear, several non-mutually exclusive mechanisms have been proposed, including the increased susceptibility to HIV/SIV infection of Th17 cells and its CD4+CCR6+ and CD4+CD161+ T cell precursors (Gosselin et al, 2010;Kader et al, 2009;Monteiro et al, 2011;Prendergast et al, 2010) and the defective generation of Th17 cells in nonnatural versus natural hosts. Very recent and unpublished observations suggest that loss of CD4+IL-21+ T cells and CD103+ dendritic cells, with reduced availability of IL-21 or retinoic acid, respectively, may significantly contribute to Th17 cell depletion in SIV-infected rhesus macaques (Cervasi B et al, CROI 2011;Klatt N et al, Keystone 2011).…”
Section: Preservation Of Th17 Cells and Mucosal Integritymentioning
confidence: 99%